Termination of Pregnancy: Misoprostol Versus Prostaglandin E2 - Imama Tul Bushra; Faiza Ibrar; Saima Qamar; Atikka Masud; Touseef Fatima; Seema Gul (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy of vaginal Misoprostol and vaginal prostaglandin E2 in termination of pregnancy.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Obstetrics & Gynecology, Fauji Foundation Hospital, Islamabad, Pakistan, from Apr to Oct 2021.Methodology: After taking informed consent, a total of 80 women between the age of 20-40 years were included in the study for termination of pregnancy. Molar or ectopic pregnancy, signs of septic abortion, Chronic Liver Disease, and bleeding disorders were excluded. In group A, a 200µgm tablet of Misoprostol was inserted intravaginal every 6 hours, a total of 4 doses, while in group B patients, a PGE2 3 mg tablet was inserted intravaginal, a total of 4 doses. All patients in both groups were evaluated after 24 hours, at which efficacy was noted. Results: The mean age of women in Group-A was 27.18±3.81 years, and in Group-B was 27.18±4.96 years. The mean gestational age in Group-A was 11.83±3.24 weeks, and in Group-B was 12.20±3.30 weeks. In this study, efficacy (complete expulsion of the fetus within 24 hours of medication) was seen in 37 (92.50%) women in Group-A (Vaginal Misoprostol) and 29 (72.50%) women in Group-B (Vaginal prostaglandin E2) with a p-value of 0.019.Conclusion: This study concluded that the efficacy of vaginal Misoprostol is better in termination of pregnancy as compared to vaginal prostaglandin E2.